Skill and performance - Grugulis, Irena (2011)
Examines the link between skill and performance. Concludes with recommendations for academics, policy makers and society to inter alia, engage in more sensitive and socialised enquiry; find integrated solutions incorporating firms or particular sections of the labour instead of dependence on education as the sole means to prevent or reduce poverty and adopt a more democratic, egalitarian and socially inclusive society.